The Clinical Implications of Thyroid Hormones and its Association with Lipid Profile: A Comparative Study from Western Nepal - Mittal, Ankush; Sathian, Brijesh; Kumar, Arun; Chandrasekharan, Nishida; Dwedi, Sanjeev (Nepal Journal of Epidemiology, 2010)
Background Thyroid dysfunction is one of the major public health problems in Nepal. Laboratory tests facilitate early diagnosis before clinical features are obvious, increased sensitivity carries the price of decreased diagnostic specificity. Laboratory tests coupled with supportive clinical findings are frequently used to diagnose thyroid dysfunction. Historically, hypercholesterolemia and raised serum low density lipoprotein (LDL) cholesterol levels have been found to be associated with subclinical hypothyroidism. Therefore, assessment of altered lipid profile plays a supportive role in diagnosis of thyroid dysfunction. The aim of our study was to find out the variations of thyroid hormones and lipid profile in hyperthyroidism and hypothyroidism with their clinical implications. Materials and Methods It was a hospital based retrospective study carried out from the data retrieved from the register maintained in the Department of Biochemistry of the Manipal Teaching Hospital, Pokhara, Nepal between 1st July, 2009 and 30th June, 2010. The variables collected were age, gender, T4, T3, TSH, fT4, total cholesterol and triglyceride levels. Descriptive statistics and testing of hypothesis were used for the analysis of data. Results 122 out of the 365 subjects selected for the study had some form of thyroid disorder. Of the 122 cases, 40 had hyperthyroidism, 42 had hypothyroidism and the remaining 40 were diagnosed to have subclinical hypothyroidism. The frequency of thyroid disorders was much higher in females as compared to their male counterparts. The mean value of each variable in cases, except for age, was statistically significant as compared to controls (p=0.001). Elevated levels of total T3 (CI 2.14 to 2.59), T4 (CI 13.00 to 15.30) and fT4 (CI 2.51 to 2.81) associated with decreased TSH levels (CI 0.29 to 0.35) were found in cases of hyperthyroidism. The TSH values (CI 17.05 to 22.85) were markedly increased while T4 and T3 values were found to be less than the reference range in cases of hypothyroidism. There was significant increase in the mean concentration of total cholesterol (CI 268.83 to 289.79) and triglycerides (CI 154.81to 182.05) in cases of hypothyroidism. The fT4 (CI 1.08 to 1.22) levels were in reference range and TSH levels (CI 9.59 to 10.50) were moderately raised in cases of subclinical hypothyroidism. Conclusion Thyroid dysfunction is common across all age groups and shows a strong female preponderance in Pokhara valley. It necessitates the measurement of thyroid hormones in women after the age of 50, in pregnancy and after delivery, and in women and men with hypercholesterolemia. Therefore, timely screening and check ups are necessary in order to curtail the problem of undiagnosed cases, giving specific consideration to patients who have high artherogenic profile. This will reduce the risk of future negative health events in older adults. Key Words: Thyroid hormones; Hyperthyroidism; Hypothyroidism; Lipid profile; Nepal DOI: 10.3126/nje.v1i1.4102 Nepal Journal of Epidemiology 2010;1 (1):11-16